The Effect of Positions of Vertical Glass Fins inside a Double Skin Façade Air Cavity as Acoustical Barriers and Ventilation Potentials. (2016) - Lee, Jeehwan; Mohamed, Haider; Chang, Jae D.
Abstract: A number of studies state that natural ventilation strategies can contribute to improving indoor air quality (IAQ) and thermal comfort; however, noise annoyance by urban traffic noise transmission is a significant challenge that leads to the degradation of the acoustical quality in urban environments. As a solution to meet both needs for natural ventilation benefits and noise transmission loss via ventilation openings, a Double Skin Façade (DSF) as a case study was analyzed. Another study demonstrated that vent openings of DSFs allowed a decrease in acoustical performance of DSF air cavities because airborne noise transmitted via vent openings travels both horizontally and vertically. Therefore, research scope aims to simulate thermal performance of air cavity by the stack effect and noise transmission loss by verticals glass fins using FloVENT 9.3 and SoundFlow respectively. The test cases of CFD simulation study are designed based on different spatial volumes of DSF air cavity partitioned by vertical glass fins, affecting changes of air temperature and airflow inside air cavities. The CFD simulation data resulted in that DSF air cavity ratios of length to depth divided by vertical glass fins influence the efficiency of heat dissipation inside DSF air cavities. It was observed that air temperature in CASE 4, which has the ratio of 8 meters in length to 1 meter in depth of a DSF air cavity, has the higher potential of an overheating problem than that of CASE 1 (1 meter in length to 1 meter in depth) and CASE 2 (2 meters in length to 1meter in depth). CASE 1 and CASE 2 produced relatively lower the mean air temperature inside DSF air cavities through the efficient heat dissipation. In addition, it was found that the thicker the vertical glass fins are, the higher the Sound Transmission Loss (STL) values are shown.